2009
DOI: 10.1007/s00467-009-1213-y
|View full text |Cite
|
Sign up to set email alerts
|

Urinary tract infections: to prophylaxis or not to prophylaxis?

Abstract: Urinary tract infections, with or without reflux, are the most frequent reason for long-term antibacterial prophylaxis in infants and children. When one is considering the use of prophylaxis in these children, what is clear from existing published data? Up to 2006 there were a small number of poor quality studies, with no reliable evidence of the effectiveness of antibiotics in preventing recurrent symptomatic urinary tract infections (UTIs). Since then, four randomised controlled studies, to assess the benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 15 publications
2
30
0
5
Order By: Relevance
“…Las guías de 1999 de la AAP fueron modificadas sobre la base del cuestionamiento del beneficio de la profilaxis antibiótica rutinaria, del reconocimiento de que el RVU no era el único responsable del daño renal, de que los pacientes que evolucionaban a la cronicidad solían presentar patología estructural congénita y de los costos que generaba el estudio sistemático de todos los casos. 3,[13][14][15][16] El abordaje más selectivo propuesto en 2011, si bien reduce el número de CUGM negativas, 6 también generó preocupación en relación con la posibilidad de que se retrasara el diagnóstico de patología relevante, 7 especialmente sabiendo que la ecografía es un método con baja sensibilidad y especificidad para detectar RVU. 8,17,18 Apoyando esto, K. D. Suson y R. Mathews encontraron que el 62% de los pacientes de entre 2 y 24 meses con ecografía renal normal luego de la primera ITU, sin considerar si había sido atípica, presentaba RVU ≥ grado III y que el 17% también tenía escaras renales.…”
Section: Discussionunclassified
“…Las guías de 1999 de la AAP fueron modificadas sobre la base del cuestionamiento del beneficio de la profilaxis antibiótica rutinaria, del reconocimiento de que el RVU no era el único responsable del daño renal, de que los pacientes que evolucionaban a la cronicidad solían presentar patología estructural congénita y de los costos que generaba el estudio sistemático de todos los casos. 3,[13][14][15][16] El abordaje más selectivo propuesto en 2011, si bien reduce el número de CUGM negativas, 6 también generó preocupación en relación con la posibilidad de que se retrasara el diagnóstico de patología relevante, 7 especialmente sabiendo que la ecografía es un método con baja sensibilidad y especificidad para detectar RVU. 8,17,18 Apoyando esto, K. D. Suson y R. Mathews encontraron que el 62% de los pacientes de entre 2 y 24 meses con ecografía renal normal luego de la primera ITU, sin considerar si había sido atípica, presentaba RVU ≥ grado III y que el 17% también tenía escaras renales.…”
Section: Discussionunclassified
“…The 1999 AAP guidelines were modified based on the following: the benefit of routine antibiotic prophylaxis was questioned, VUR was recognized as not being the only cause of kidney damage, patients who developed a chronic disease tended to have a congenital structural condition, and the high costs associated with studying all patients systematically. 3,[13][14][15][16] The more selective approach proposed in 2011 reduced the number of negative VCUGs, 6 but also generated concern in relation to the potential delay in the diagnosis of a relevant pathology, 7 especially because the renal ultrasonography is a method with low sensitivity and specificity to detect VUR. 8,17,18 In support of these observations, K. D. Suson and R. Mathews observed that 62% of patients aged between 2 and 24 months old with normal ultrasonography after the first UTI -without considering if it was an atypical UTI-had grade III VUR or higher, and that 17% also had renal scarring.…”
Section: Discussionmentioning
confidence: 99%
“…None of the patients with normal DMSA scintigraphy had high grade VUR according to these reports. The discrimination of the high and low grade (grade 1, 2) reflux is important since high grade reflux generally need surgical correction [9].…”
Section: Bilateralmentioning
confidence: 99%